2012
DOI: 10.1038/nrn3229
|View full text |Cite
|
Sign up to set email alerts
|

Impaired mitochondrial function in psychiatric disorders

Abstract: Major psychiatric illnesses such as mood disorders and schizophrenia are chronic, recurrent mental illnesses that affect the lives of millions of individuals. Although these disorders have traditionally been viewed as 'neurochemical diseases', it is now clear that they are associated with impairments of synaptic plasticity and cellular resilience. Although most patients with these disorders do not have classic mitochondrial disorders, there is a growing body of evidence to suggest that impaired mitochondrial f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
311
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 409 publications
(333 citation statements)
references
References 172 publications
13
311
0
2
Order By: Relevance
“…Furthermore, we have shown that this GR dependent regulation of mitochondrial mRNA can occur in response to environmental stress, a known factor in a number of neurologic and psychiatric diseases (41). These findings have implications for a variety of phenomena in neuroscience, from synaptic plasticity, by which local control of mitochondrial activity could be altered, to neurodegenerative diseases in which mitochondrial dysfunction is widely implicated and in which stress can be a contributing factor (10,42). Acute Immobilization Stress.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we have shown that this GR dependent regulation of mitochondrial mRNA can occur in response to environmental stress, a known factor in a number of neurologic and psychiatric diseases (41). These findings have implications for a variety of phenomena in neuroscience, from synaptic plasticity, by which local control of mitochondrial activity could be altered, to neurodegenerative diseases in which mitochondrial dysfunction is widely implicated and in which stress can be a contributing factor (10,42). Acute Immobilization Stress.…”
Section: Discussionmentioning
confidence: 99%
“…NCALD, also known as VSNL3, is a high-affinity Ca 2 þ sensor that has been found to interact with cytoskeletal proteins (Paterlini et al, 2000). In SCZ, evidence for brain mitochondrial dysfunction has been reported, including findings of impaired brain energy metabolism, developmental deviations, abnormal neurotransmission, and connectivity (Manji et al, 2012;Rosenfeld et al, 2011), along with mitochondrial hypoplasia, oxidative phosphorylation system imbalance, and altered mitochondrial protein expression (Karry et al, 2004;Prabakaran et al, 2004). Consistent with these reports, we detected alterations of several subunits of the electron transport chain complex I in the frontal cortex tissue from PCP-treated rats (NDUFA9, NDUFS3, NDUFV1, and NDUFV2).…”
Section: Biological Functions P-values Proteins Biological Functions mentioning
confidence: 99%
“…Mitochondria, the source of 95% of the ATP in the brain, are involved in many brain disorders including SZ (Anglin et al, 2012;Manji et al, 2012). Mitochondria function as a dynamic network constantly undergoing fusion and fission, the balance of which is important in maintaining their structural integrity and function (Legros et al, 2002 a role in mitochondrial fusion and contributes to the maintenance and operation of the mitochondrial network (Bach et al, 2003).…”
Section: Introductionmentioning
confidence: 99%